88.5k views
2 votes
Raj is simplifying (5^4)^3 using these steps:

(5^4)3 =5^4 x 5^4 x 5^4= 5^4+4+4

Although Raj is correct so far what could he have done instead to simplify the expression (5^4)^3 ?

User NikkyD
by
6.6k points

2 Answers

5 votes

(a^(x))^(y)= a^(x*y) \\ \\So, (5^(4))^(3)= 5^(4*3) = 5^(12)
User Vinuthan
by
5.8k points
2 votes

Answer:

Instead of simplifying the expression using the given steps Raj could directly apply property of exponents


(5^4)^3=5^(12)

Explanation:

Given raj has an expression
(5^4)^3 and he simplifies this using the given steps.

He can do the following steps to simplify the above expression

Consider the given expression
(5^4)^3

Using property of exponents,
(a^m)^n=a^(m\cdot n)

Thus, the given expression beecomes,


(5^4)^3=5^(4 \cdot 3)=5^(12)

Thus, raj obtained the same answer only his calculation reduces,


(5^4)^3=5^(12)

Instead of simplifying the expression using the given steps Raj could directly apply property of exponents




User Igor Voynov
by
6.0k points